Tragic elements in absurd theater - Luaibi Saad, Haider; Abbas Ali, Fouad (International Journal of Psychosocial Rehabilitation, 2020)
Tragedy is a term that has a variety of meanings and applications in criticism and literary history. In drama, it refers to a particular kind of play, the definition of which is established by Aristotle in his Poetics. Aristotle’s definition remains among the best and is often used as background against which later tragedies are to be analyzed. However, many plays, which have been written after Aristotle, do not conform completely to his definition. The purpose of this paper is to trace the changes that the concept of tragedy has been undergoing from the early beginnings of its emergence as a literary genre in Greek theater to the modern age, where the various dramatic changes that people experience make the formulation of a new concept of tragedy a must. The discussion of the concept of tragedy in post-war drama is the major concern of the second section. The major dramatic movement that dominates post-war drama is The Theatre of Absurd. In fact, the dramatic conventions that mark this theater serve primarily to shatter the traditional conventions of the naturalistic or fourth-wall drama: sequential plot, dialogue, realistic characters, and setting. The second section is concluded with an analysis of Samuel Beckett’s Endgame, which conveys the tragic sense in modern man’s experience, which emerges as a reaction to the collapse of moral and social values in modern Western culture.